2016
DOI: 10.1007/s12298-016-0368-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different host associations on glutamine synthetase activity and ammonium transporter in Santalum album L.

Abstract: The present study was aimed at understanding the role of different hosts in ammonium transporter1;2 expressions and glutamine synthetase(GS) activity and their effects on the growth parameters in the sandal. Sandal plant associated with leguminous host expressed better growth parameters. GS activity of leguminous hosts alone and in host associated sandals was analyzed using GS transferase assay. Highest GS activity was expressed in Mimosa pudica-sandal association compared to other leguminous and non-leguminou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The antioxidant enzyme activities in S. album leaves grown with the host were significantly stronger than those grown without a host. Deepa and Yusuf also confirmed that the host could improve the enzyme activities in S. album leaves [ 6 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The antioxidant enzyme activities in S. album leaves grown with the host were significantly stronger than those grown without a host. Deepa and Yusuf also confirmed that the host could improve the enzyme activities in S. album leaves [ 6 ].…”
Section: Discussionmentioning
confidence: 92%
“…However, in the subsequent seedling growth process, its root system must parasitize the roots of appropriate host plants; otherwise, S. album will not grow in a healthy manner and ultimately dies. Planting hosts with S. album seedlings could significantly increase the total lengths, surface areas, and dry weights of S. album seedling roots and the total N, total P, and total K contents in whole plants [ 6 ]. Radomiljac et al [ 7 ] found that the longer S. album seedlings and hosts grow together in a nursery before planting in the field, the larger the height, stem diameter, total plant dry weight, and shoot and root dry weight were after planting in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a host plant for sandalwood has been proven to be essential in the root association through haustoria formation for supplying water and other available nutrients to improve morphological growth (Deepa and Yusuf 2016). Sandalwood develops strategy by modifying the roots to form haustorium when in physical contact with the roots of the host plants.…”
Section: Nutrients Fact Of Sandalwoodmentioning
confidence: 99%